Strategies in activating lymphatic system on symptom distress and health-related quality of life in patients with heart failure: secondary analysis of a pilot randomized controlled trial - Liu, Ruixia; Fang, Jinbo; Fu, Mei R.; Meng, Qingtong; Li, Minlu; Zhang, Xiaoxia; Allred, Sarah R.; Li, Yuan (Frontiers in Cardiovascular Medicine, 2023)
Background Abnormal interstitial fluid accumulation remains the major cause for patients with heart failure (HF) to endure a myriad of distressing symptoms and a decline in their health-related quality of life (HRQoL). The lymphatic system is essential in regulating fluid balance within the interstitial compartment and has recently been recognized as an important target for the prevention and mitigation of congestion. This study aimed to investigate the effects of exercises in activating lymphatic system on symptom distress and HRQoL among patients with HF. Methods and results This was a pre-determined, secondary analysis of the TOLF-HF [The-Optimal-Lymph-Flow for Heart Failure (TOLF-HF)] study, a two-arm pilot randomized controlled trial evaluating the preliminary effects of the lymphatic exercise intervention in enhancing interstitial decongestion among patients with HF. Participants were randomized to receive either a four-week TOLF-HF program in addition to standard care or standard care alone. The Chinese version of the Minnesota Living with Heart Failure Questionnaire (MLHFQ) was employed to measure symptom distress and HRQoL before and after the intervention. Data analyses included descriptive statistics, the independent sample t-test, Pearson’s chi-square test, the Mann-Whitney U test, and covariance analysis. Of the 66 patients enrolled, 60 completed the study. The study results exhibited that the TOLF-HF intervention were effective in alleviating both physical and psychological symptom distress. The intervention group yielded significantly lower MLHFQ total scores in comparison to the control group. The odd ratio of achieving meaningful improvement in HRQoL in TOLF-HF group was 2.157 times higher than those in the control group. Conclusions The TOLF-HF program focusing on activating lymphatic system was effective in alleviating physical and psychological symptom distress as well as improving HRQoL for patients with HF. The tolerability, feasibility, and effectiveness of the TOLF-HF intervention make it a promising intervention for patients to manage HF. Clinical Trial Registration http://www.chictr.org.cn/index.aspx, identifier (ChiCTR2000039121).